Joint Transmit Waveform and Receive Mismatched Filter Design to Suppress Range Sidelobe - Hairui Wang; Haihong Tao; Tiantian Zhong; Wendi Li (Remote Sensing)
Pulse compression technology can augment the likelihood of target discernment without degradation and without amplifying system hardware requisites. However, radar-communication integrated waveforms may cause mismatches in reception due to communication modulation, leading to increased loss in processing gain (LPG). This method aims to achieve communication transmission while suppressing near-range sidelobe interference (NRSI) with a minor sacrifice in LPG. An environment-based weighted mismatched filter (EWMF) design methodology is proposed to attenuate NRSI to the requisite level, with further control of LPG possible by adjusting communication modulation parameters. Moreover, the alternating direction method of multipliers is employed to jointly optimize the integrated waveform and filter design. The effectiveness of this method is demonstrated using the average sidelobe level over a specified region as the performance metric. Theoretical evaluation and experimental results confirm the applicability of waveforms using EWMF, effectively suppressing NRSI, and this method is suitable for all waveforms based on pulse compression processing. Notably, it offers cost-reduction advantages without requiring modifications to the radar transmitter or receiver.